Dexmedetomidine Improves Cardiovascular and Ventilatory Outcomes in Critically Ill Patients: Basic and Clinical Approaches - Castillo, Rodrigo L.; Ibacache, Mauricio; Cortínez, Ignacio; Carrasco-Pozo, Catalina; Farías, Jorge G.; Carrasco, Rodrigo A.; Vargas-Errázuriz, Patricio; Ramos, Daniel; Benavente, Rafael; Torres, Daniela Henríquez; Méndez, Aníbal (Frontiers in Pharmacology, 2020)
Dexmedetomidine (DEX) is a highly selective α2-adrenergic agonist with sedative and analgesic properties, with minimal respiratory effects. It is used as a sedative in the intensive care unit, the operating room, and occasionally in other locations. The opioid-sparing effect and the absence of respiratory effects make dexmedetomidine an attractive adjuvant drug for anesthesia in obese patients who are at an increased risk for postoperative respiratory complications. The pharmacodinamic effects on the cardiovascular system are known, however the mechanisms that induce cardioprotection are still under study. Regarding the pharmacokinetics properties, this drug is extensively metabolized in the liver by the uridine diphosphate glucuronosyltransferases. It has a relatively high hepatic extraction ratio, and therefore, its metabolism is dependent on liver blood flow. This review shows, from a basic clinical approach, the evidence supporting the use of dexmedetomidine in different settings, from the use in animal models of ischemia-reperfusion and cardioprotective signaling pathways. Pharmacokinetics and pharmacodynamics studies in obese subjects and the management of patients subjected to mechanical ventilation for avoiding the deleterious of sedation. Moreover, the clinical efficacy in patients with indication of non-invasive ventilation, and the lower incidence of delirium when compared with other sedatives. The evidence described about dexmedetomidine brings a group of Chilean pharmacologists and clinicians, who have worked for more than 10 years on the subject of α2-adrenergic agonists and support independent lines of research, both in animal models and in clinical practice with patients.